2017
DOI: 10.1007/s00198-017-4286-7
|View full text |Cite
|
Sign up to set email alerts
|

Teriparatide for treatment of patients with bisphosphonate-associated atypical fracture of the femur

Abstract: There is a preliminary signal for greater improvements with immediate teriparatide therapy vs delayed therapy. However, because an AFF is a rare event, and only a small number of patients were included, the results must be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Teriparatide therapy significantly shortened the healing time and resulted in a reduced incidence of delayed healing or nonunion compared with non‐teriparatide therapy. The pro‐healing effect of teriparatide therapy on AFFs was compared between patients with immediate initiation and a delay of 6 months . In that study, radiographic bone healing at 6 and 12 months was assessed in 13 women with AFFs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Teriparatide therapy significantly shortened the healing time and resulted in a reduced incidence of delayed healing or nonunion compared with non‐teriparatide therapy. The pro‐healing effect of teriparatide therapy on AFFs was compared between patients with immediate initiation and a delay of 6 months . In that study, radiographic bone healing at 6 and 12 months was assessed in 13 women with AFFs.…”
Section: Resultsmentioning
confidence: 99%
“…The pro-healing effect of teriparatide therapy on AFFs was compared between patients with immediate initiation and a delay of 6 months. (76) In that study, radiographic bone healing at 6 and 12 months was assessed in 13 women with AFFs. The study found that immediate teriparatide initiation promoted healing of AFFs more than delayed initiation did.…”
Section: Pth Effects On Healing Of Atypical Femoral Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The papers included in the review are reported by category in Table 2. (15)(16)(17)25,26,(29)(30)(31)(32)(33) 205 Bone substitutes (41,42,45,46,48) 331 Growth factors (53,(55)(56)(57)(58) 615 Cell therapies (66,69,73) 69 Pharmacological therapy (97)** (98)(99)(100)(101)(102)(103)(104)(105)(107)(108)(109)(110)(111)(112)(113)(114) 110 ** Systematic review including case series and case reports.…”
Section: Resultsmentioning
confidence: 99%
“…In their series, the patients who received 20 µg of daily teriparatide for 6 to 24 months had an improvement in bone turnover markers serum levels, but, on the other hand, there was no significant effect on fracture healing. More recently, Greenspan et al reported the result of a pilot randomized clinical trial of 13 patients, to determine the correct timing of teriparatide administration after an AFF [101]. They found a trend in better healing rates in the group of patients who received immediate therapy with teriparatide compared to the group who received teriparatide therapy with a 6-month delay.…”
Section: Parathormone Analoguesmentioning
confidence: 99%